FPGA Based Bluetooth Controlled Land Vehicle - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper represents the utilization of Field Programmable Gate Arrays (FPGA) chip for Bluetooth controlled land vehicle. Bluetooth controlled land vehicle is developed utilizing VHDL and acknowledged in Basys-3 FPGA using Xilinx Web-Pack Vivado 18.1. The navigation and control of the vehicle is executed remotely through an Android cell phone which is taking the advantage of the built-in Bluetooth module. Any Android wireless device can be used for remote controlling of the vehicle. Android has a solid exhibit of network choices containing Wi-Fi, Bluetooth, and remote information over a cell association. Android cell phones give access to an extensive variety of valuable libraries and apparatuses that can be utilized as a part of numerous applications. Also, the Bluetooth module is an open standard particular for a radio recurrence based, short-run network innovation. Remote control of this Bluetooth controlled land vehicle operates at a maximum baud rate of 54600 bps. © 2018 IEEE.
Keywords: Android smartphone; Basys-3 board; Bluetooth module; Direct-Current (DC) Motors; FPGA; VHDL